Kualitas Pelayanan Publik Di Kecamatan Kaliorang Kabupaten Kutai Timur Provinsi Kalimantan Timur (Suatu Studi Pelayanan Administrasi Kependudukan Di Kecamatan Kaliorang) - Nanik Pujiastuti (Universitas 17 Agustus 1945 Samarinda, 2016)
Quality of service is a State-related capability meets the desires of customers so the gap between the expectations with the reality of the case. Quality should be started from the need of customers and end on customer perception. Dotted with decline in the explanation above, the authors are interested in conducting research with the title